A History of the Tuna-Dolphin Problem: Successes, Failures, and Lessons Learned - Ballance, Lisa T.; Gerrodette, Tim; Lennert-Cody, Cleridy E.; Pitman, Robert L.; Squires, Dale (Frontiers in Marine Science, 2021)
Multispecies aggregations of tuna, dolphins, and seabirds are prevalent and conspicuous in the vast waters of the eastern tropical Pacific and form the basis of a commercial fishery for yellowfin tuna through setting on schools of dolphins, which is among the largest tuna fisheries in the world. Incidental dolphin mortality associated with the development and early years of the fishery was high; by 1993 it was estimated that eastern spinner dolphins (Stenella longirostris orientalis) had been reduced to 44% and northeastern offshore spotted dolphins (S. attenuata attenuata) to 19% of pre-fishery levels. Efforts to reduce this mortality began at the inception of the fishery and comprised a diverse array of approaches: modifications to fishing methods and fishing gear (backdown, Medina panel, high-intensity floodlights, swimmers to disentangle and release dolphins); U.S. legislation (through the U.S. Marine Mammal Protection Act, MMPA, and subsequent amendments); international agreements (including the International Dolphin Conservation Program that established dolphin mortality limits, and the legally-binding multilateral Agreement on the International Dolphin Conservation Program); and economic incentives (notably through establishment of the U.S. dolphin-safe label and positive certification by the Marine Stewardship Council). Together, these bycatch mitigation efforts have been remarkably successful; dolphin mortality due to entanglement as recorded by fisheries observers (hereafter, entanglement mortality) has been reduced by >99%. Despite this, the degree to which dolphin populations have recovered remains unclear. Multiple lines of evidence indicate that individual dolphins experience multiple sets in their lifetimes and although causality has not been established, research suggests that chase and encirclement might have impacts on dolphins in addition to entanglement mortality. These impacts potentially include increased fetal and/or calf mortality, separation of nursing females and their calves, decreased fecundity, increased predation, disruption of mating and other social systems, and ecological disruption. The strong management emphasis on monitoring entanglement mortality, and the infrastructure necessary to support this monitoring (in particular, 100% observer coverage on large purse-seiners) require funding to the extent that other activities, particularly continued surveys to monitor stock status and clarify the potential influence of other effects of the fishery on dolphin populations, are currently inadequately funded.